55.9k views
1 vote
Solve the system of equations.

x + 3y = −1
2x + 2y = 6

(−4, 1)
(2, −1)
(4, −1)
(5, −2)

User Fvillalba
by
5.9k points

1 Answer

2 votes
x + 3y = −1
2x + 2y = 6

x + 3y = −1
x +3y -3y = -1 +3y
x= -1 +3y

2x + 2y =6
2(-1 - 3y) + 2y = 6
-2 -6y + 2y = 6
-2 -4y =6
-2+2 -4y = 6+2
-4y = 8
-4y/-4= 8/-4
y = -2

2x + 2y = 6
2x + 2(-2) = 6
2x + -4 = 6
2x -4 +4 = 6+4
2x = 10
2x/2 = 10/2
x = 5

Check

2x + 2y = 6
2(5) + 2(-2) = 6
10 + -4 = 6
6 = 6

So the answer is (5,2)
User Evan Hahn
by
5.1k points